Asymptomatic Becker muscular dystrophy in a family with a multiexon deletion - Ferreiro, Verónica (2009)
We report a Becker muscular dystrophy (BMD) family with one 5-year-old affected patient and a 69-year-old asymptomatic grandfather. Dystrophin gene multiplex polymerase chain reaction and multiplex ligation-dependant probe amplification analysis showed that both males carried an in-frame deletion of exons 45-55. Segregation analysis revealed two additional asymptomatic boys in this family. Our finding supports previous predictions that exons 45-55 are the optimal multiexon skipping target in antisense gene therapy to transform the severe Duchenne muscular dystrophy into the milder BMD, or even asymptomatic, phenotype.